The relative age effect in European professional soccer: Did ten years of research make any difference? - Helsen, W. F.; Baker, J.; Michiels, S.; Schorer, J.; Van Winckel, J.; Williams, A. M. (Journal of Sports Sciences, 2012)
The relative age effect (RAE) refers to an asymmetry in the birth-date distribution favouring players born early in the selection year and discriminating against participants born later in the year. While the RAE effect was initially reported in sport more than two decades ago, there have been few attempts to examine whether player selection strategies have changed over time in light of our improved understanding of the phenomenon. We compared the birth-date distributions of professional soccer players in ten European countries over a 10-year period involving the 2000/2001 and 2010/2011 competitive seasons, respectively. Chi-square goodness-of-fit tests were used to compare differences between the observed and expected birth-date distributions across selection years. Generally, results indicated no change in the RAE over the past 10 years in professional soccer, emphasizing the robust nature of this phenomenon. We propose a change in the structure of youth involvement in soccer to reduce the impact of the RAE on talent identification and selection.